Effects of hibiscus sabdariffa Linn. aqueous extract on oxidative stress and T lymphocyte population in spleen of streptozotocin-induced diabetic rats - Nor Malia Abd Warif; Asyraf Akmal Ayob; Wan Marahaini Wan Razali; Siti Balkis Budin; Muhd Hanis Md Idris; Satirah Zainalabidin; Jamaludin Mohamed (penerbit ukm, 2014)
Disturbances in immune system contribute to chronic infection among diabetic patients. Hibiscus sabdariffa L. (roselle) fruit extract has been scientifi cally proven to possess antioxidant, antidiabetic and antiinfl ammatory properties. The aim of this study was to investigate the effects of H. sabdariffa fruit extract against oxidative stress parameter and T lymphocyte population in spleen of streptozotocin (STZ) induced diabetic rats. Male Sprague-Dawley rats were injected with 45 mg/kg STZ to induce diabetic condition and further treated with 100 mg/kg H. sabdariffa fruit aquoeus extract daily for 28 days. Spleen was harvested to determine the oxidative stress indicators and quantifi cation of T lymphocytes. The results showed a signifi cant decreased in the number of spleen cells and spleen weight in the diabetic rats compared with control rats. However, there were no signifi cant changes in the level of malondialdehyde (MDA), protein carbonyl and superoxide dismutase (SOD) activity the percentage of spleen CD3+ CD4+ and CD3+ CD8+ T lymphocytes amongst groups of study. In addition, histology observation showed no pathological alteration in spleen histology of diabetic rats. The fi ndings suggested that aqueous extract of H. Sabdariffa fruit supplementation has no effect on the oxidative stress and the percentage of CD3+ CD4+ and CD3+ CD8+ T lymphocytes in spleen of diabetic rats.